Developing robot transporter learning media to learn microcontroller - I Gusti Putu Asto Buditjahjanto; Chandra Ainur Rizqi; Bambang Suprianto (Jurnal Pendidikan Vokasi, 2020)
Learning media play a role in bridging the interaction between the teacher and students. Using learning media can help students to understand the material delivered by the teacher more efficiently. Al Kholiliyah, a Vocational High School in Bangkalan, Indonesia, still lacks interactive learning media to motivate students in learning. The robot transporter as an interactive learning medium can be applied to solve the lack of learning media that engage students in learning. The purpose of this study is to analyze the validity of the robot transporter as learning media, to analyze the validity of the learning plan (a syllabus, a lesson plan, a student worksheet)  of robot transporter learning media, and to analyze the student response of the usage robot transporter learning media. The validation results of the robot transporter learning media show that the value of the validity is 3.89, categorized as very valid. The validity of the syllabus is 3.78, categorized as very valid, the validity of the lesson plan is 3.88, categorized as very valid, and the validity of the student worksheets is 3.89, categorized as very valid. The results of student responses show that there are two responses: strongly agree and 28 responses with the category of agree. Based on the robot transporter validity, the learning plan validity, and the student response, it can be concluded that the robot transporter can be used in the teaching and learning process.